Optimizing Dietary Net Energy for Maximum Profitability in Growing- Finishing Pigs - J. Soto; M. D. Tokach; S. S. Dritz; M. A. Goncalves; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; U. A. Orlando (Kansas Agricultural Experiment Station Research Reports, 2017)
Feed accounts for a significant portion of swine production cost, with dietary energy alone representing more than half of the total cost. Considering the financial implications of determining the energy content of the diet, the objective of this research project was to develop a tool to accurately estimate the dietary NE content that yields maximum profitability for growing-finishing pigs. A Microsoft Excel®-based model was developed to contrast dietary NE defined by the user with recommended concentrations that are intended to maximize profitability in user defined production and economic scenarios. To calculate pig performance, the model uses prediction equations for ADG and feed efficiency. In addition, the model also uses the NDF content of the diet because of its effect on dressing percentage. For profitability calculations, a non-linear mathematical programming model was designed to select the optimum dietary NE content that yields the greatest income over total cost per pig on a live or carcass basis. The model can be used to predict dietary NE content that yields the highest economic benefit considering dynamic productive and economic scenarios. The model can be downloaded at www.ksuswine.org.
Keywords: Net energy; neutral detergent fiber; linear programming